2014
DOI: 10.1002/mus.24497
|View full text |Cite
|
Sign up to set email alerts
|

Spinal muscular atrophy: Diagnosis and management in a new therapeutic era

Abstract: Spinal muscular atrophy (SMA) describes a group of disorders associated with spinal motor neuron loss. In this review we provide an update regarding the most common form of SMA, proximal or 5q SMA, and discuss the contemporary approach to diagnosis and treatment. Electromyography and muscle biopsy features of denervation were once the basis for diagnosis, but molecular testing for homozygous deletion or mutation of the SMN1 gene allows efficient and specific diagnosis. In combination with loss of SMN1, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
348
0
40

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(392 citation statements)
references
References 126 publications
4
348
0
40
Order By: Relevance
“…1,3 It has been shown that another gene, SMN2, codes for a protein similar to that encoded by the SMN1 gene and multiple copies of SMN2 can somewhat compensate for the loss of the SMN1 gene and alleviate the severity of clinical symptoms observed. 5,6 SMA is classified into several types based on the age of onset of the disease and the degree of motor function achieved by the affected individual. 1,3 Approximately 50% of patients diagnosed with SMA have type I, which has an early onset; these infants usually do not survive beyond the first 2 years without intervention.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 It has been shown that another gene, SMN2, codes for a protein similar to that encoded by the SMN1 gene and multiple copies of SMN2 can somewhat compensate for the loss of the SMN1 gene and alleviate the severity of clinical symptoms observed. 5,6 SMA is classified into several types based on the age of onset of the disease and the degree of motor function achieved by the affected individual. 1,3 Approximately 50% of patients diagnosed with SMA have type I, which has an early onset; these infants usually do not survive beyond the first 2 years without intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, death ensues within the first 2 years of life. There are no approved treatments for SMA other than supportive care (2)(3)(4). SMA results from insufficient levels of the survival motor neuron (SMN) protein (5), which is produced by expression of the SMN1 and SMN2 genes.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Prenatal diagnosis of SMA is critical for couples who are heterozygous for SMN1 gene deletion, although screening must be limited to families who already have children with SMA (or SMA presence in the extended family). We must remember that there is a significant de novo mutation rate (1.7%).…”
Section: Discussionmentioning
confidence: 99%